The adoption of technology in Higher/ Nursing Education - S M Meyer (AOSIS, 2001)
This is a review article on the adoption of technology in higher education. Higher education in general is looked at. Nursing Education is also higher education and therefore it will not be addressed separately, but mentioned in some instances. The article presents a look into how students and lecturers experience change, as well as barriers they perceive in the integration and adoption of technology. Some suggestions are made to the adoption process as well as the necessity for personnel development in information technology. The role that Information Technology personnel play in the adoption and integration process of technology is also discussed.